Pre-exposure Prophylaxis Uptake Among Men Who Have Sex With Men Who Used nPEP: A Longitudinal Analysis of Attendees at a Large Sexual Health Clinic in Montréal (Canada). (1st December 2020) - Xia, Yiqing; Greenwald, Zoë R.; Milwid, Rachael M.; Trottier, Claire; Boissonnault, Michel; Gaul, Neil; Charest, Louise; Landry, Gabrielle; N. Zahedi, Navid; Szabo, Jason; Thomas, Réjean; Maheu-Giroux, Mathieu
Abstract : Background: Reducing HIV transmission using pre-exposure prophylaxis (PrEP) requires focussing on individuals at high acquisition risk, such as men who have sex with men with a history of nonoccupational post-exposure prophylaxis (nPEP). This study aims to characterize longitudinal trends in PrEP uptake and its determinants among nPEP users in Montréal. Methods: Eligible attendees at Clinique médicale l'Actuel were recruited prospectively starting in October 2000 (nPEP) and January 2013 (PrEP). Linking these cohorts, we characterized the nPEP-to-PrEP cascade, examined the determinants of PrEP uptake after nPEP consultation using a Cox proportional-hazard model, and assessed whether PrEP persistence differed by nPEP history using Kaplan–Meier curves. Results: As of August 2019, 31% of 2682 nPEP cohort participants had 2 or more nPEP consultations. Subsequent PrEP consultations occurred among 36% of nPEP users, of which 17% sought nPEP again afterward. Among 2718 PrEP cohort participants, 46% reported previous nPEP use. Among nPEP users, those aged 25–49 years [hazard ratio (HR) = 1.3, 95% confidence interval (CI): 1.1 to 1.7], with more nPEP episodes (HR = 1.4, 95% CI: 1.3 to 1.5), who reported chemsex (HR = 1.3, 95% CI: 1.1 to 1.7), with a sexually transmitted infection history (HR = 1.5; 95% CI: 1.3 to 1.7), and who returned for their first nPEP follow-up visit (HR = 3.4, 95% CI: 2.7 to 4.2) had higher rates of PrEP linkage. There was no difference in PrEP persistence between nPEP-to-PrEP and PrEP only participants. Conclusion: Over one-third of nPEP users were subsequently prescribed PrEP. However, the large proportion of men who repeatedly use nPEP calls for more efficient PrEP-linkage services and, among those who use PrEP, improved persistence should be encouraged.